The impact of sociological and environmental factors for dengue infection in Kuala Lumpur, Malaysia - Adnan, Ruhil A.; Ramli, M. F.; Othman, Hidayatulfathi; Ash'aari, Zulfa Hanan; Syed Ismail, S. N.; Samsudin, Suhailah (Elsevier BV, 2021)
Background: Dengue incidence has grown dramatically around the world in recent years. Vector control is the only method to reduce dengue incidence due to the lack of a vaccine available. By understanding the factors contributed to the vector densities such as environmental and sociological factors, dengue prevention and control may succeed. Objective: This study is aimed at determining the impact of sociological and environmental factors contributing to dengue cases. Methods: The study surveyed 379 respondents with dengue history. The socio-environmental factors were evaluated by chi-square and binary regression. Result: The chi-square results revealed sociological factors associated between family with dengue experience such as older age (p =0.012), fewer than four people in the household (p= 0.008), working people (p= 0.004) and apartment/terrace houses (p=0.023). Similarly, there is a significant association between respondent’s dengue history and houses that are shaded with vegetation (p= 0.012) and the present of public playground areas near the residential (p = 0.011). Conclusion: The study identified socio-environmental factors that play an important role in the abundance of Aedes mosquitoes and also for the local dengue control measures.